2016
DOI: 10.3329/ijns.v4i1.28592
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Repeat Breeding in Commercial Dairy Farms of Chittagong District of Bangladesh

Abstract: The study was conducted to measure the prevalence of repeat breeding cows and to identify the potential risk factors of Repeat breeding syndrome in commercial dairy farms at Chittagong of Bangladesh during July 2011 to October 2012. A total of 15 government registered dairy farms having 283 cows were surveyed for individual and farm level variables identified using preset questionnaire. Out of them 56 dairy cows was sampled for bacteriological exploration and culture sensitivity test. Overall prevalence of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
1
8
3
Order By: Relevance
“…Many other studies also supported the present finding of highest sensitivity for ciprofloxacin as 75 per cent (Moharana et al, 2000), 83.33 per cent (Ingawale et al, 2003), 93.75 per cent (Mane et al, 2009), 75 per cent (Reddy et al, 2012), 71.05 per cent (Bhat et al, 2013) while Nath et al, (2014) and Rohit et al, (2019) reported lower sensitivity of 45.90 per cent and 63.50 per cent, respectively than the present study. Zaman et al, (2015) also observed highest sensitivity for ciprofloxacin and enrofloxacin (100%).…”
Section: In-vitro Antibiotic Susceptibility Test Of Uterine Bacterial Isolatessupporting
confidence: 82%
See 1 more Smart Citation
“…Many other studies also supported the present finding of highest sensitivity for ciprofloxacin as 75 per cent (Moharana et al, 2000), 83.33 per cent (Ingawale et al, 2003), 93.75 per cent (Mane et al, 2009), 75 per cent (Reddy et al, 2012), 71.05 per cent (Bhat et al, 2013) while Nath et al, (2014) and Rohit et al, (2019) reported lower sensitivity of 45.90 per cent and 63.50 per cent, respectively than the present study. Zaman et al, (2015) also observed highest sensitivity for ciprofloxacin and enrofloxacin (100%).…”
Section: In-vitro Antibiotic Susceptibility Test Of Uterine Bacterial Isolatessupporting
confidence: 82%
“…While Udayavel et al, (2013) observed lower sensitivity (32%) to enrofloxacin. Bhat et al, (2013), Kavyashree (2013), Udhayavel et al, (2013) and Nath et al, (2014) reported that large number of isolates was sensitive to ceftriaxone (67.11%, 40.26%, 64.00% and 89.20%, respectively) than observed in the present study. Less number of isolates (10.17) were sensitive in the studies by Rohit et al, (2019).…”
Section: In-vitro Antibiotic Susceptibility Test Of Uterine Bacterial Isolatescontrasting
confidence: 40%
“…However, according to Nath et al . [ 28 ], higher experience in animal husbandry can help breeders in overcoming the challenges that arise when managing the farm. This agrees with our result that breeding experience has a significant relationship with the occurrence of repeat breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Private entrepreneurs and some Non-Government Organizations (NGOs) mainly operate the diary sector in Bangladesh. Chittagong is the second largest city of Bangladesh and a dense of dairy zone (Nath et al, 2014). Not only that, Chittagong is one of the dairy producing emerged areas of Bangladesh, where dairy farming has been traditionally an important and major component.…”
Section: Introductionmentioning
confidence: 99%